2000
DOI: 10.1016/s1097-2765(00)00051-4
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Cascade of the Nuclear Receptors FXR, SHP-1, and LRH-1 Represses Bile Acid Biosynthesis

Abstract: Bile acids repress the transcription of cytochrome P450 7A1 (CYP7A1), which catalyzes the rate-limiting step in bile acid biosynthesis. Although bile acids activate the farnesoid X receptor (FXR), the mechanism underlying bile acid-mediated repression of CYP7A1 remained unclear. We have used a potent, nonsteroidal FXR ligand to show that FXR induces expression of small heterodimer partner 1 (SHP-1), an atypical member of the nuclear receptor family that lacks a DNA-binding domain. SHP-1 represses expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

52
1,348
4
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,705 publications
(1,416 citation statements)
references
References 48 publications
52
1,348
4
12
Order By: Relevance
“…Previous studies have shown that SHP mediates some of the regulatory activities exerted by FXR (33,36,46,47). SHP is an atypical nuclear receptor, lacking a ligand-binding domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that SHP mediates some of the regulatory activities exerted by FXR (33,36,46,47). SHP is an atypical nuclear receptor, lacking a ligand-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is circumstantial evidence to link the activity of FXR to the regulation of bile acid synthesis from cholesterol, providing a link between nutrient absorption and regulation of key steps in the intermediate metabolism. In addition, because bile acids might be toxic for the liver, activation of FXR by natural and synthetic ligands has been shown to prevent bile acid-induced liver toxicity in a variety of rodent models (33)(34)(35)(36)(37)(38)(39). The homeostatic function of FXR in the liver is highlighted by the demonstration that mice harboring a disrupted FXR (FXR Ϫ/Ϫ ) develop spontaneously an array of hepatocellular abnormalities including adenomas and carcinomas.…”
mentioning
confidence: 99%
“…Subsequently, SHP binds to the liver receptor homolog-1 (LRH-1, NR5A2) which is a potent activator of CYP7A1. This interaction decreases the transcriptional activity of LRH-1 and subsequently -11 -lowers CYP7A1 transcription [72,73]. Surprisingly, bile acids are able to repress Cyp7a1 expression in SHP -/-animals suggesting the presence of redundant mechanisms [74,75].…”
Section: Nuclear Receptor Regulation Of Cholesterol Biosynthesis and mentioning
confidence: 98%
“…Upon activation, FXR alters the transcription of target genes by interacting with FXR-responsive elements as a heterodimer with the 9-cis-retinoic acid receptor (14). In liver cells, FXR negatively regulates genes involved in bile acid synthesis and lipidogenesis but enhances the expression/activity of a number of the basolateral transporters required for bile formation and cholesterol and lipid secretion (15). In intestinal epithelial cells, FXR activates the transcription of the intestinal bile acid-binding protein (I-BABP) (16) and fibroblast growth factor 15 (17), with both genes regulating key aspects of liver and intestinal homeostasis.…”
mentioning
confidence: 99%